THE INFLUENCE OF TELEMEDICINE SERVICES, PATIENT TRUST, AND SATISFACTION ON INTEREST IN USING DIGITAL HEALTH PLATFORMS - Jeanny Kathleen Hartini; Vip Paramarta; Kosasih; Farida Yuliaty (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of telemedicine services, patient trust, and satisfaction on interest in using digital health platforms. In the digital age, healthcare platforms such as telemedicine offer easy access to medical services, but the adoption of these platforms is influenced by several factors, including patient trust and satisfaction with services. Patient trust relates to their perception of data security and service quality, while satisfaction is influenced by the user's experience during interaction with the platform. The method used in this study is literature review by collecting data from relevant journals and articles published between 2019 and 2023. Data is obtained through international and national databases such as PubMed, Google Scholar, and Scholar. The results show that all three variables have an interrelated role in influencing patients' interest in using digital health platforms. Effective and accessible telemedicine services provide convenience that encourages patients to switch to digital platforms. Patients' confidence in data security and service quality further increases their convenience in using this platform. Patient satisfaction built from positive experiences while interacting with the platform will encourage them to continue using the service.